Analysis of the performance of the brazilian intellectual property system: challenges and perspectives - Vasconcelos, Cleiton Rodrigues de; Silva, Daniel Pereira da (Revista Gestão & Tecnologia, 2018)
The protection of intellectual property (IP) is a crucial area to support the development process of any country, as it is in this context that the biggest strategic disputes are taking place. In recent years Brazil has developed some actions to achieve greater efficiency in the public IP management system, but are we on the right track? The present study seeks to present answers regarding the performance of Brazil and to highlight the advances and challenges regarding the IP system. The methodological approach was structured based on a review in the literature, highlighting the scientific, economic and technological indicators on the development of IP and the main IP objects registered with the Brazilian national intellectual property body (INPI) in the period of 2013 to 2016, in the areas of patents, trademarks, industrial design, computer program, circuit topography, technology contracts and geographical indication.